Associations of nm23H1, VEGF-C, and VEGF-3 Receptor in Human Prostate Cancer - Zui-Su Yang; Yin-Feng Xu; Fang-Fang Huang; Guo-Fang Ding (Molecules, 2014)
We studied the expression of the non-metastatic clone 23 type 1 (nm23H1) gene, vascular endothelial growth factor (VEGF)-C, and its receptor VEGFR-3 using an in situ hybridization technique and immunohistochemical analyses with prostate cancer tissues and adjacent benign tissues of 52 human archival cases. The association between VEGF-C expression, microlymphatic count (MLC), and staining intensity for nm23H1 and VEGFR-3 was used to evaluate tumor metastasis and survival rate. MLC values were significantly higher in tumorous tissue than in non-cancerous tissue. VEGF-C mRNA, VEGFR-3, and nm23H1 were highly expressed in tumorous tissue. VEGFR-3 expression was greater in VEGF-C mRNA-positive tumors than in VEGF-C mRNA-negative tumors. The association of VEGFR-3 expression with VEGF-C mRNA and MLC suggested that the poor prognosis and tumor metastasis associated with VEGFR-3 expression may be due, in part, to its role in promoting angiogenesis. VEGF-C expression was significantly associated with tumor lymphangiogenesis, angiogenesis, and immune response as a potent multifunctional stimulating factor in prostate cancer. Expression of nm23H1 was significantly inversely correlated with lymph node metastasis. Furthermore, there was a strong negative correlation between the expression of nm23H1, VEGF-C mRNA, and MLC. These findings provide important information for prophylactic, diagnostic, and therapeutic strategies for prostate cancer.